2024
DOI: 10.1128/jb.00420-23
|View full text |Cite
|
Sign up to set email alerts
|

Control of asparagine homeostasis in Bacillus subtilis : identification of promiscuous amino acid importers and exporters

Janek Meißner,
Manuel Königshof,
Katrin Wrede
et al.

Abstract: The Gram-positive model bacterium B. subtilis is able to import all proteinogenic amino acids from the environment as well as to synthesize them. However, the players involved in the acquisition of asparagine have not yet been identified for this bacterium. In this work, we used d -asparagine as a toxic analog of l -asparagine to identify asparagine transporters. This revealed that d - but not l … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 58 publications
(109 reference statements)
2
9
0
Order By: Relevance
“…6 , AexA expression resulted in increased tolerance to all three amino acids indicating that AexA is also active in the export of these amino acids. The contribution of an aerA * mutation to serine resistance has been described in a recent study ( 23 ), and the results reported here demonstrate that this is caused by the increased expression of AexA in the mutant. We can thus conclude that AexA is a non-specific amino acid exporter for C3-amino acids.…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…6 , AexA expression resulted in increased tolerance to all three amino acids indicating that AexA is also active in the export of these amino acids. The contribution of an aerA * mutation to serine resistance has been described in a recent study ( 23 ), and the results reported here demonstrate that this is caused by the increased expression of AexA in the mutant. We can thus conclude that AexA is a non-specific amino acid exporter for C3-amino acids.…”
Section: Resultssupporting
confidence: 79%
“…2 ). This observation suggests that AimA also imports β-alanine in addition to serine, glutamate, and aspartate ( 12 , 15 , 23 ).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations